2016
DOI: 10.1097/bcr.0000000000000317
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral and Photoplethysmography Optical Imaging Techniques Identify Important Tissue Characteristics in an Animal Model of Tangential Burn Excision

Abstract: Burn excision, a difficult technique owing to the training required to identify the extent and depth of injury, will benefit from a tool that can cue the surgeon as to where and how much to resect. We explored two rapid and noninvasive optical imaging techniques in their ability to identify burn tissue from the viable wound bed using an animal model of tangential burn excision. Photoplethysmography (PPG) imaging and multispectral imaging (MSI) were used to image the initial, intermediate, and final stages of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…Given that 75% of dermis is composed of collagen, others have targeted the dermis for evaluation, but have been unable to consistently characterize thermally injured collagen. Some authors insist that collagen can be evaluated with H&E alone; however, characteristics of collagen in H&E‐stained tissue that correlate with denaturation have been variously described as glass‐like or as a separation of collagen . In other cases, authors do not provide detailed descriptions of collagen changes, other than identifying the entire section as necrotic, despite the presence of epithelial lined appendages with a normal appearance .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that 75% of dermis is composed of collagen, others have targeted the dermis for evaluation, but have been unable to consistently characterize thermally injured collagen. Some authors insist that collagen can be evaluated with H&E alone; however, characteristics of collagen in H&E‐stained tissue that correlate with denaturation have been variously described as glass‐like or as a separation of collagen . In other cases, authors do not provide detailed descriptions of collagen changes, other than identifying the entire section as necrotic, despite the presence of epithelial lined appendages with a normal appearance .…”
Section: Introductionmentioning
confidence: 99%
“…Some authors insist that collagen can be evaluated with H&E alone; however, characteristics of collagen in H&E-stained tissue that correlate with denaturation have been variously described as glass-like 9 or as a separation of collagen. 10 In other cases, authors do not provide detailed descriptions of collagen changes, other than identifying the entire section as necrotic, despite the presence of epithelial lined appendages with a normal appearance. 8 Furthermore, studies that advocate more complex staining methods such as Masson's Trichrome or polarization light evaluation of Picrosirius red-stained tissue may mislead interpretation of collagen health, as these techniques mainly identify changes in collagen fiber alignment and can be dependent on the timing of the burn injury.…”
Section: Introductionmentioning
confidence: 99%
“…In one of our recent studies using a pig model of burn excision, we demonstrated that burn-injured tissue was detec-tible with *85% accuracy and the viable wound bed to which a skin graft could be applied is detectible by MSI with 87% accuracy. 82 Analysis of the spectral difference between burn-injured tissue and wound bed tissue revealed that reflectance spectra vary most significantly at wavelengths of 515, 669, 750, and 972 nm, suggesting that burn tissues' blood, extracellular matrix, and water components makeup are quite different from healthy skin. 92 …”
Section: Msi and Hyperspectral Imagingmentioning
confidence: 99%
“…The result has been favorable in validation testing where we found an average of 87% accuracy in the classification of tissues relevant to diagnose the preparedness of a wound bed in a burn surgery animal model. 82 …”
Section: Msi Data Analysismentioning
confidence: 99%
See 1 more Smart Citation